2021
DOI: 10.31234/osf.io/c2ytm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are There Cross-Cultural Legal Principles? Modal Reasoning Uncovers Procedural Constraints on Law

Abstract: Despite pervasive variation in the content of laws, legal theorists and anthropologists have often argued that all laws share certain abstract features and even speculated that law may be a human universal. In the present report, we contribute cross-cultural data to this debate: Are there essential features of law? Participants in ten different countries (N = 2844) were asked whether there could be laws that violate certain procedural principles (e.g., laws applied retrospectively or unintelligible laws), and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…More recently though, Hannikainen, Tobia, et al. (2021) reported that some of these earlier findings apply across different cultures, languages and legal systems. In the newer study, participants from a mix of 11 civil and common law countries assessed Fullerian principles either as actual statements about the laws (e.g., whether the laws violated each of the Fullerian principles) or as statements about the possible and necessary features of laws (e.g., whether the laws could violate the eight principles).…”
Section: General Concepts Of Legal Philosophymentioning
confidence: 89%
See 3 more Smart Citations
“…More recently though, Hannikainen, Tobia, et al. (2021) reported that some of these earlier findings apply across different cultures, languages and legal systems. In the newer study, participants from a mix of 11 civil and common law countries assessed Fullerian principles either as actual statements about the laws (e.g., whether the laws violated each of the Fullerian principles) or as statements about the possible and necessary features of laws (e.g., whether the laws could violate the eight principles).…”
Section: General Concepts Of Legal Philosophymentioning
confidence: 89%
“…This suggests that certain intuitions about the concept of law are robust across languages, cultures, and legal systems. According to the authors, “people consistently believe that laws necessarily abide by a series of procedural principles: they could not retroactively punish past conduct, be kept secret, or be incomprehensible to most, for instance” (Hannikainen, Tobia, et al., 2021, p. 10).…”
Section: General Concepts Of Legal Philosophymentioning
confidence: 99%
See 2 more Smart Citations
“…The 2021 study sought to discover whether this response pattern would hold for a more diverse set of respondents. Whereas Donelson and Hannikainen (2020) relied on Anglophone respondents from the United States, Hannikainen et al (2021) selected speakers from the United States, the United Kingdom, and nine non-Anglophone countries. In those non-Anglophone countries, experiments were conducted in a non-English language commonly spoke in the relevant country.…”
Section: Summarizing the Recent Workmentioning
confidence: 99%